Risk factors of pulmonary tuberculosis in Indonesia: A case-control study in a high disease prevalence region - Fahdhienie, Farrah; Mudatsir, Mudatsir; Abidin, Taufik F.; Nurjannah, Nurjannah (Narra Sains Indonesia, 2024)
Tuberculosis (TB) remains one of the most widespread infectious diseases in the world, with high mortality and morbidity rates, contributing to a significant disease burden, particularly in developing countries. The aim of this study was to determine the risk factors of TB among the population aged 17 years (late adolescent) and above in one of the high TB prevalence countries, Indonesia. A case-control study was conducted in Banda Aceh, Indonesia, involving newly diagnosed pulmonary TB patients who visited one of the eleven community health centers in Banda Aceh. The controls were individuals matched by age and sex who lived near the cases and had no TB infection. A total of 16 risk factors were assessed. Hierarchical multivariable logistic regression models were used to examine the association between the risk factors and the occurrence of TB. A total of 196 cases and 196 controls were included in the study. Multivariable logistic regression analysis identified 11 independent predictors for the occurrence of TB after controlling possible confounders. Patients who lived in houses with insufficient light exposure were 77 times more likely to develop TB compared to those living in houses with sufficient light exposure (adjusted odds ratio (AOR): 77.69; 95%CI: 27.09, 222.79). The study also showed that people who had close contact with TB patients (AOR: 25.39; 95%CI: 2.10, 306.52), had poor knowledge of TB (AOR: 24.2; 95%CI: 6.89, 85.17), had comorbidities (AOR: 4.49; 95%CI: 1.35, 14.89), insufficient food utilization (AOR: 3.41; 95%CI: 1.51, 7.71), negative preventive behavior (AOR: 3.39; 95%CI: 1.49, 7.72), low education level (AOR: 3.08; 95%CI: 1.26, 7.55), and insufficient housing humidity (AOR: 2.89; 95%CI: 1.18, 7.12) were associated with increased the odds of having TB. Being employed, having income above minimum wage, and having good nutritional intake were protective factors for developing TB. In conclusion, the determinants of TB among people aged 17 years and older are a clear indication of the need for TB prevention programs targeting not only individual risk factors but also environmental risk factors, particularly providing adequate housing conditions. This study provided useful information that might help to develop and adopt effective policies for TB control in Indonesia.